Characteristics of Interventions to Improve Bone Health in Children With Cerebral Palsy: A Systematic Review. Issue 2 (18th April 2022) - Liquori, Brianna M.; Gannotti, Mary E.; Thorpe, Deborah E.; Fuchs, Robyn K.
Abstract : Purpose: A systematic review evaluated exercise parameters and ages that produced the most improvement in bone among individuals with cerebral palsy (CP) ages 3 to 21 years. Methods: PubMed, Scopus, Ebscohost, and Web of Science identified potential articles. Covidence was used to identify eligible citations and assess bias. The osteogenic index (OI) was used to evaluate intervention parameters. Results: The database search identified 312 citations. Twelve full-text articles were included. A 1-hour calisthenic exercise program performed 2 to 3 times a week for 8 months targeting each body region had the highest effect size and a substantial OI. Most of the interventions reviewed had low OIs. Activities of longer duration and greater intensity had greater OIs and prepubertal age-enhanced treatment effects. Conclusion: Bone interventions for individuals with CP have low OIs, and principles of mechanostat theory should be applied to exercise dosing.